RANCANGAN SEQUENCE PENAMBANGAN PADA BLOK A4 PT. ADHI KARTIKO PRATAMA DESA LAMERURU KECAMATAN LANGGIKIMA KABUPATEN KONAWE UTARA PROVINSI SULAWESI TENGGARA - Sarfin.L, Wiil; Anshari, Erwin; Rizky Awaliah N, Wd. (Jurnal Locus Penelitian dan Pengabdian, 2023)
Adhi Kartiko Pratama is a private company which operates in the nickel mining sector and has a Mining Business License covering an area of 1975 Ha. To maintain the company's production, currently PT. AKP plans to open a new mining location in Front Block A, especially in Sub Block A4, with a production target of 100,000 tons per month. This research aims to design a mining sequence based on production targets in Block A4. The design created is an estimated ore distribution. Minable reserves based on the mining pit limit design in Block A4 are 466,383.36 bcm with a total tonnage of 769,532.54 tons with an average Ni content of 1.76%, and including mining recovery parameters of 90%, it is 419,745, 02 bcm and a tonnage of 692,579.29 tons with an average Ni content of 1.74%, then the estimated mine life in Block A4 PT. Adhi Kartiko Pratama will last approximately 6 months. Based on the production target in Block A4, the mining sequence design is divided into 6 stages carried out using a level plan system or following excavation levels, where mining will start from topography with the highest level of 180 meters above sea level to topography with the lowest level of 135 meters above sea level.